2019
DOI: 10.3389/fmicb.2019.00608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sequential Acclimation to Various Carbon Sources on the Proteome of Acetobacter senegalensis LMG 23690T and Its Tolerance to Downstream Process Stresses

Abstract: Acetic acid bacteria are very vulnerable to environmental changes; hence, they should get acclimated to different kinds of stresses when they undergo downstream processing. In the present study, Acetobacter senegalensis LMG 23690 T , a thermo-tolerant strain, was acclimated sequentially to different carbon sources including glucose (condition Glc), a mixture of glucose and ethanol (condition EtOH) and a mixture of glucose and acetic acid (condition GlcAA). Then, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
0
9
0
2
Order By: Relevance
“…As the acetous fermentation progresses, different stresses impact the function, cultivability and viability of acetic acid production (Shafiei, Delvigne, & Thonart, 2013; Shafiei, Delvigne, Babanezhad, et al, 2013). In addition, different conditions during the upstream process, such as growth in the presence of different carbon sources or growth at a low pH, may affect the resistance of cells to stresses during the downstream process (Shafiei et al, 2019).…”
Section: Status Of Research On the Acetobacter Senegalensis Strainmentioning
confidence: 99%
See 4 more Smart Citations
“…As the acetous fermentation progresses, different stresses impact the function, cultivability and viability of acetic acid production (Shafiei, Delvigne, & Thonart, 2013; Shafiei, Delvigne, Babanezhad, et al, 2013). In addition, different conditions during the upstream process, such as growth in the presence of different carbon sources or growth at a low pH, may affect the resistance of cells to stresses during the downstream process (Shafiei et al, 2019).…”
Section: Status Of Research On the Acetobacter Senegalensis Strainmentioning
confidence: 99%
“…It was shown that the tolerance of AAB to high concentrations of ethanol and acetic acid (as the two main stressors) is dependent on several factors, such as the pH of the culture medium, available soluble oxygen, temperature, available nutrients and strains used (Ndoye, Weekers, et al, 2007; Ndoye et al, 2009). Shafiei et al (2019) showed that, in addition to the above‐mentioned factors, the acclimation of A. senegalensis cells in different carbon sources definitely affects the utilization of ethanol. In other words, A. senegalensis can grow in a culture medium containing glucose as the main carbon source.…”
Section: Status Of Research On the Acetobacter Senegalensis Strainmentioning
confidence: 99%
See 3 more Smart Citations